Molnupiravir: a new hope in the treatment of COVID-19 - Paudel, Rama (International Journal of Basic & Clinical Pharmacology, 2022)
Coronavirus disease-19 (COVID-19), a highly contagious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been causing pandemic since its first emergence in Wuhan, China in December 2019.1 Most of the people with COVID-19 experience mild to moderate respiratory illness and recover without requiring special treatment. The common presentations of the disease include fever or chills, cough, shortness of breath or difficulty breathing, fatigue, muscle or body aches, headache, new loss of taste or smell, sore throat, congestion or runny nose, nausea or vomiting and diarrhea.2 However, upto 20% patients develop severe disease requiring hospitalization.3 Older adults and people with underlying medical conditions like heart or lung disease or diabetes are at higher risk for developing more serious complications such as pneumonia, acute respiratory distress syndrome, cardiac injury, arrhythmia, septic shock, liver dysfunction, acute kidney injury, multi-organ failure and death of the patients.2,4 The pandemic has presented a major threat to public health worldwide. As of 13 March 2022, World Health Organization (WHO) reported a total of 452,201,564 confirmed cases of COVID-19 with 6,029,852 deaths (case fatality: 1.33%).5